Induksi Polifenol Mahkota Dewa dan Apoptosis Sel Kanker Paru Mencit Strain Balb/C: Analisis pada Up-Regulation Bax dan Down-Regulation Bcl-2 - Theopilus W Watuguly; Tjahjono Tjahjono; Martha Kaihena; Syahran Wael (MEDIA MEDIKA INDONESIANA, 2012)
Mahkota Dewa polyphenol induction and apoptosis cell lung cancer in Balb/c strain mice analysis on up-regulation bax and downregulation Bcl-2Background: This research is aimed to prove the role of Mahkota Dewa polyphenol in the up-regulation Bax and down-regulation in strain Balb/c mice which inducted with benzo(a)pyrene (BaP).Method: Post test control group design with 30 strain Balb/c mice sample, aged 1-2 weeks, weighed 20-30 grams, healthy mice condition. All mice inducted with BaP and then randomized into 2 groups, which were the control group and the treatment group (polyphenol 50mg). The development of the lung carcinogenesis was observed by tissue surgery in the 8th, 17th and 26th week. The data collected include expression examination Bax and Bcl-2. The data analysis was conducted by Kruskal-Wallis, Mann-Whitneyand correlation test of Spearman's with significance degree of p<a (0.05).Result: The oral administration of Mahkota Dewa polyphenol of 50 mg were significantly decreased the occurance of lung carcinogenesis through decreasing of protein Bax and increasing Bcl-2 in treatment group in week 8, 17 and 26 (p=0.000). Protein Bax for the control group for week 8 were 4.04±0.22 and 1.92±0.10 in week 26, while the treatment group were 5.96±0.32 and 4.68±0.22 (p=0.000). Protein Bcl-2 for the control group for week 8 were 5.80±0.32 and 9.64±0.26 in week 26, while the treatmentgroup were 5.12±0.22 and 7.38±0.21 (p=0.000). The Spearman correlation for Bax and Bcl-2 with significancy value of (p=0.000).Conclusion: The administration of Mahkota Dewa polyphenol of 50 mg effectively increased Bax protein expression and decreased Bcl-2 protein expression in mice Balb/c.Keywords: Polyphenol, Mahkota Dewa (Phaleria macrocarpa [Scheff.] Boerl), protein Bax, protein Bcl-2, strain Balb/c mice, benzo(a)pyrene (BaP)ABSTRAKLatar belakang: Penelitian ini bertujuan membuktikan peran polifenol Mahkota Dewa dalam meningkatkan protein Bax dan menurunkan protein Bcl-2 pada mencit strain Balb/c hasil induksi Benzo(a)pyrene (BaP).Metode: Post test only control group design dengan sampel 30 mencit strain Balb/c, umur 1-2 minggu, berat 20-30 gram, kondisi mencit sehat. Semua mencit diinduksi BaP kemudian hewan dirandomisasi menjadi 2 kelompok yaitu kelompok kontrol dan kelompok perlakuan polifenol 50 mg. Perkembangan karsinogenesis paru diamati dengan pembedahan jaringan pada minggu ke-8, 17 dan 26. Data dikumpulkan meliputi pemeriksaan ekspresi Bax dan Bcl-2. Analisis data dengan Kruskal-Wallis dilanjutkan denganuji Mann-Whitney dan uji korelasi Spearman dengan derajat kemaknaan p<a (0,05).Hasil: Pemberian oral polifenol Mahkota Dewa sebesar 50 mg secara bermakna memperlihatkan peningkatan protein Bax dan penurunan protein Bcl-2 pada kelompok perlakuan pada minggu ke-8, 17 dan 26 (p=0,000). Protein Bax pada kelompok kontrol minggu ke-8 sebesar 4,04±0,22 dan 1,92±0,10 minggu ke-26, sedangkan kelompok perlakuan sebesar 5,96±0,32 dan 4,68±0,22 (p=0,000) sedangkan protein Bcl-2 pada kelompok kontrol minggu ke-8 sebesar 5,80±0,32 dan 9,64±0,26 minggu ke-26, sedangkan kelompok perlakuan sebesar 5,12±0,22 dan 7,38±0,21 (p=0,000). Hasil uji korelasi Spearman protein Bax dan protein Bcl-2 dengan nilai significancy (p=0,000).